English Pronunciation, Intonation, and Accent Reduction for Japanese Speakers - Azkiyah, Hayatul; Putri, Hilma Pami; Eliza, E; Syafitri, Widya (Program Studi Pendidikan Bahasa Inggris, ISDIK Kie Raha Maluku Utara, 2023)
The purpose of this study was to review the book of English Pronunciation, Intonation, and Accent Reduction for Japanese Speakers. This research applied library research method to review a book related to technique in teaching English pronunciation. Data were prepared and analyzed using data reduction, data display and drawing the conclusion. The review result of this research were the book is recommended and appropriate as new pronunciation guides and online courses, and learn tips and technique for teaching and learning English pronunciation, intonation and accent reduction. The advantages of this book is a practical and user-friendly guide that provides specific advice and exercises to help Japanese speakers improve their English pronunciation. The writer also give application and online link related to the material. The book is designed specifically for Japanese speakers, so it may not be as helpful for learners from other language backgrounds. This book may be too technical for readers who do not have a background in phonetics or linguistics. It also more focused on prounciation aspects rather than overall langugae acquisition, so the readers may need to seek other sources to strengthen their English language skills as a whole.